CFA-4-a fluorinated metal-organic framework with exchangeable interchannel cations - Fritzsche, J.; Grzywa, M.; Denysenko, D.; Bon, Volodymyr; Senkovska, Irena; Kaskel, Stefan; Volkmer, Dirk (Dalton Transactions, 2017)
The syntheses and crystal structures of the fluorinated linker 1,4-bis(3,5-bis(trifluoromethyl)-1H-pyrazole-4-yl)benzene (H2-tfpb; 1) and the novel metal-organic framework family M[CFA-4] (Coordination Framework Augsburg University-4), M[Cu5(tfpb)3] (M = Cu(i), K, Cs, Ca(0.5)), are described. The ligand 1 is fully characterized by single crystal X-ray diffraction, photoluminescence-, NMR-, IR spectroscopy, and mass spectrometry. The copper(i)-containing MOF crystallizes in the hexagonal crystal system within the chiral space group P6322 (no. 182) and the unit cell parameters are as follows: a = 23.630(5) Å, c = 41.390(5) Å, V = 20 015(6) Å3. M[CFA-4] features a porous 3-D structure constructed from pentanuclear copper(i) secondary building units CuI5(pz)6- (pz = pyrazolate). Cu(I)[CFA-4] is fully characterized by synchrotron single crystal X-ray diffraction, thermogravimetric analysis, variable temperature powder X-ray diffraction, IR spectroscopy, photoluminescence and gas sorption measurements. Moreover, thermal stability and gas sorption properties of K[CFA-4] and Cu(I)[CFA-4] are compared.
CRIS-Team Scopus Importer:2022-04-14